Trajectories of Ethnic‐Racial Discrimination Among Ethnically Diverse Early Adolescents: Associations With Psychological and Social Adjustment. Issue 6 (23rd October 2014) - Niwa, Erika Y.; Way, Niobe; Hughes, Diane L.
<x xml:space="preserve">Abstract</x> Using longitudinal data, the authors assessed 585 Dominican, Chinese, and African American adolescents (Grades 6–8, Mage at W1 = 11.83) to determine patterns over time of perceived ethnic‐racial discrimination from adults and peers; if these patterns varied by gender, ethnicity, and immigrant status; and whether they are associated with psychological (self‐esteem, depressive symptoms) and social (friend and teacher relationship quality, school belonging) adjustment. Two longitudinal patterns for adult discrimination and three longitudinal patterns for peer discrimination were identified using a semiparametric mixture model. These trajectories were distinct with regard to the initial level, shape, and changes in discrimination. Trajectories varied by gender and ethnicity and were significantly linked to psychological and social adjustment. Directions for future research and practice are discussed.